Experimental Study on the Damage and Degradation Characteristics of Red Sandstone after Dry and Wet Cycling by Low Magnetic Field Nuclear Magnetic Resonance (NMR) Technique - Yuan Zhao; Jiangteng Li; Gang Ma (Geofluids)
To study the damage evolution of rocks under the action of wet and dry cycles, nuclear magnetic resonance (NMR) technology was used to test red sandstone under different times of wet and dry cycles. The T2 spectral distribution curve, porosity, spectral peak area, and damage distribution curve of the rock were obtained, and the quantitative relationship between porosity, damage degree, and number of cycles was established. The results show that with the increase of the number of wet and dry cycles, the T2 spectral curve of rock gradually moves to the right, but the moving amplitude gradually decreases. The porosity and spectral area increase with the increase of the number of wet and dry cycles, coupled with a declining growth rate, and the maximum increase in porosity is 18.789%. The damage degree of rock increase with the increase of the number of cycles, but with the continuous increase of the number of cycles, the damage rate decreases, and finally the damage degree of rock tends to be a constant value.